Philosophy and science fiction - French, Peter A.; Wettstein, Howard K. (Midwest studies in philosophy, 2015)
"Science Fiction and Philosophy deals with science-fictional thought experiments and their long history in philosophy, with roots back to the mythological inventions of ancient philosophers such as Plato and Zhuangzi. These thought experiments play a prominent role especially in current metaphysical theorizing about personal identity, artificial minds, and the nature of time. This issue includes reflections on the nature of science fiction, on the epistemology of science fictional thought experiments, on our possible moral and social relationships with future intelligent beings, on the prospects of human or post-human self-transformation, and on time travel. While most of the contributions are expository essays written in the typical style of journal articles, two of the contributions are original short stories written by prominent SF writers whose writing is informed by the advanced graduate work they have done in philosophy" -- Provided by publisher.